Volleyball Smash Ability Level of the Athletes of the Medan Women's Club Volleyball - Purba, Andi Nata; Nurkadri, Nurkadri; Sitepu, Indra Darma (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2022)
The purpose of this study was to determine the level of smash ability of the athletes of the Women's Volleyball Club. This research is a descriptive study with the research population at the Bina Putri Volleyball Club with the sampling technique using the total sampling technique, which means the number of samples is 10 people. The instrument used to measure the ability to smash is the Nurhasan smash attack instrument. From the tests carried out, the results of the athlete's smash ability were obtained with an average score of 6.6. The average score obtained shows that the smash ability of the athletes of the Bina Putri Medan Volleyball Club is included in the less category with a value of 2. One of the factors causing the low smash ability of the athletes of the Bina Putri Medan Volleyball Club is the weak explosive power of the athletes' leg muscles. These results indicate that it is necessary to carry out exercises aimed at increasing the explosive power of the leg muscles regularly and continuously in an effort to increase the explosive power of the leg muscles.